2020
DOI: 10.3389/fphar.2020.00849
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Vascular Endothelial Growth Factor Therapy as an Alternative or Adjunct to Pan-Retinal Photocoagulation in Treating Proliferative Diabetic Retinopathy: Meta-Analysis of Randomized Trials

Abstract: Aim: To compare anti-vascular growth factor (anti-VEGF) pharmacotherapy with panretinal photocoagulation (PRP) for proliferative diabetic retinopathy (PDR). Method: PubMed, Embase, Medline, the ClinicalTrials.gov and the Cochrane Central Register of Controlled Trials were reviewed systemically. Randomized controlled trials (RCT) on anti-VEGF therapy versus PRP or anti-VEGF agent combined with PRP versus PRP for PDR are eligible to be included. Outcome measures were regression and recurrence of neovascularizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…The CLARITY study demonstrated the advantageous effect on visual outcome at one year with a lower incidence of vitreous haemorrhage following loading treatment with aflibercept for PDR over standard PRP treatment [ 7 ]. A meta-analysis by Gao et al demonstrated fewer PDR complications with the use of anti-VEGF when compared to PRP alone [ 37 ]. Through the use of OCTA (optical coherence tomography angiography), He et al suggested that combination PRP plus anti-VEGF treatment was more effective at regressing NVE than PRP alone [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The CLARITY study demonstrated the advantageous effect on visual outcome at one year with a lower incidence of vitreous haemorrhage following loading treatment with aflibercept for PDR over standard PRP treatment [ 7 ]. A meta-analysis by Gao et al demonstrated fewer PDR complications with the use of anti-VEGF when compared to PRP alone [ 37 ]. Through the use of OCTA (optical coherence tomography angiography), He et al suggested that combination PRP plus anti-VEGF treatment was more effective at regressing NVE than PRP alone [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The CLARITY study demonstrated the advantageous effect on visual outcome at one year with a lower incidence of vitreous haemorrhage following loading treatment with a ibercept for PDR over standard PRP treatment 22 . A meta-analysis by Gao et al demonstrated fewer PDR complications with the use of anti-VEGF when compared to PRP alone 23 . Through the use of OCTA (optical coherence tomography angiography), He et al suggested that combination PRP plus anti-VEGF treatment was more effective at regressing NVE than PRP alone 24 .…”
Section: Discussionmentioning
confidence: 99%
“…54 There are other various pivotal global studies that established the effectiveness of anti-VEGF therapy. [56][57][58] Preoperative anti-VEGF injections have also been shown to decrease surgical time required, as well as being associated with reduced intraoperative bleeding. An IVB also helps in overcoming the complications of VH by minimising the need for PPV and decreasing vitreous clear-up time.…”
Section: Advantages Of Using Anti-vegf Therapy In Pdrmentioning
confidence: 99%